Review of neuroimaging findings in congenital Zika virus syndrome and its relation to the time of infection - Radaelli, Graciane (Neuroradiol J, 2020)
BACKGROUND: Many original articles and case series have been published emphasizing the neuroimaging findings of congenital Zika virus (ZIKV) infection. The majority of these studies do not follow a neuroradiological methodology to describe malformations and brain abnormalities resulting from ZIKV infection. The cause-and-effect correlation between the gestational period of maternal infection and the severity of encephalic changes at birth has rarely been reported. A systematic literature review was conducted on the neuroimaging findings in children affected with microcephaly due to ZIKV. METHODS: PubMed, Cochrane Library and Web of Science were searched for full-text articles published up to July 2019. Duplicate entries were removed. Two independent reviewers performed a quality assessment of all the studies included. RESULTS: A total of 2214 publications were identified. Of these 2170 were excluded by analysis of titles and abstracts, resulting in the inclusion of only eight articles. Chi-square and Fisher’s exact tests were performed with a 95% confidence interval to verify the statistically significant differences in the neuroradiological findings between the cases of ZIKV infection in the first or second trimester of gestation. The studies published so far have described image abnormalities at random, without utilizing any pre-established neuroradiological criteria, and imaging modalities with different sensitivity and accuracy have been used, which jeopardizes a reliable and adequate statistical analysis. CONCLUSIONS: Neuroimaging abnormalities are much more prevalent and severe when the infection by ZIKV is contracted in the first or second trimester of pregnancy.